Caregiver comprehension and satisfaction associated with informed consent for pediatric flexible bronchoscopy: A single‐center experience. Issue 2 (7th November 2022) - Simpson, Ryne; McHendry, Carolyn; Mullen, Lisa; Burg, Gregory
Abstract: Pediatric flexible bronchoscopy (FB) is a relatively common procedure performed in children with respiratory concerns. Despite this, there is no data examining the informed consent process for FB. A prospective study evaluating informed consent comprehension and satisfaction was conducted in 71 primary caregivers of children undergoing outpatient FB. Most caregivers (97%) were overall satisfied with the consent process and reported understanding the potential benefits (97%) and minor risks (94%) associated with the procedure. A smaller percentage (83%) reported understanding major risks associated with FB. Patient safety was reported as the most important aspect of the consent process. Caregivers of children undergoing FB for the first time were more likely to want additional FB‐specific information when compared to caregivers of children who had previously undergone FB (53% vs 16%, odds ratio: 5.97). In general, caregivers of children undergoing outpatient FB are satisfied with the informed consent process. Areas for improvement include ensuring adequate understanding of major risks associated with the procedure and considering a tailored approach based on the caregiver's level of experience.